If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(z + 3) + -1z = -1z + -5(z + 2) Reorder the terms: -2(3 + z) + -1z = -1z + -5(z + 2) (3 * -2 + z * -2) + -1z = -1z + -5(z + 2) (-6 + -2z) + -1z = -1z + -5(z + 2) Combine like terms: -2z + -1z = -3z -6 + -3z = -1z + -5(z + 2) Reorder the terms: -6 + -3z = -1z + -5(2 + z) -6 + -3z = -1z + (2 * -5 + z * -5) -6 + -3z = -1z + (-10 + -5z) Reorder the terms: -6 + -3z = -10 + -1z + -5z Combine like terms: -1z + -5z = -6z -6 + -3z = -10 + -6z Solving -6 + -3z = -10 + -6z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '6z' to each side of the equation. -6 + -3z + 6z = -10 + -6z + 6z Combine like terms: -3z + 6z = 3z -6 + 3z = -10 + -6z + 6z Combine like terms: -6z + 6z = 0 -6 + 3z = -10 + 0 -6 + 3z = -10 Add '6' to each side of the equation. -6 + 6 + 3z = -10 + 6 Combine like terms: -6 + 6 = 0 0 + 3z = -10 + 6 3z = -10 + 6 Combine like terms: -10 + 6 = -4 3z = -4 Divide each side by '3'. z = -1.333333333 Simplifying z = -1.333333333
| x^6+3x^3-4= | | 17x=8x+8 | | -2*-4=o | | 4x-2+2x-5=77 | | 4(5z-1)-5(2+9)=2(z+1) | | 2*-4=o | | -2*-4=ourfgn | | sin(7x)=cos(7x) | | (2d^2-9d)-(-4d^2+20d+17)= | | 2x+(18-x)=11 | | 6(-2)=r+5r | | P(x)=(60x-0.3x^2)-(5x+13) | | 3x+1/3=3x-1/2 | | ln(16x)= | | 5x+14=2+7x | | -1(-1)=z | | 2cos(3x-1)=0 | | 32=2(x+4.5) | | (c^2-9c-5)-(-c^2-8c-10)= | | (x-4)2=(x-2)2 | | x^2-10*x+13=0 | | x^2-10*x+13= | | 7v-28=9+3v-1 | | (11b^2-7)+(15b^2-b)= | | (6y-8)+(5y-3)+(6y+4)=180 | | 50=.5*20V^2 | | -26.3+0.1p=0.9+5.3 | | 2y-5x=-8 | | x*x+4x+1=32 | | -12.1+0.5p=0.9+5.3 | | ln^5+ln(2x)=5 | | -[4(7)-(14(7)+8)]=8+(9(7)+7) |